Developing Integrated Tourism and Travel System in China - Yuan Chang; Xinyan Li (CV TOPAZART, 2022)
China has a lot of tourism objects. Tourist visits from year to year have increased. The government, especially the tourism office, needs to collaborate to maintain and increase the growth of the number of tourists visiting China. This study aims to integrate information services from other parties collaborating to support tourism activities. Related parties are the tourism office, hotel, travel & tour agent, and tourism destination. The integration of information is intended to facilitate access to information by tourists following their needs. Observations run at the tourism office and destination in three different locations to obtain the needed information in Beijing, Chengdu, and Guilin. Object-oriented modelling is used for system analysis and development. A prototype is developed, integrating information between tourism office, hotel, Travel & Tourism Agent, and tourism destination. With the integration of such information, each party will obtain a marketing benefit, income, and other benefits.